2004
DOI: 10.1148/rg.245045002
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Trauma of the Pancreas and Biliary Tract: A Multimodality Imaging Approach to Diagnosis

Abstract: Injuries of the pancreas, gallbladder, and bile ducts due to blunt trauma are relatively uncommon and difficult to detect but are associated with high morbidity and mortality, especially if diagnosis is delayed. Accurate and early diagnosis is imperative, and imaging plays a key role in detection. Knowledge of the mechanisms of injury, the types of injuries, and the roles of various imaging modalities is essential for prompt and accurate diagnosis. Early recognition of disruption of the main pancreatic duct is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 28 publications
3
112
0
9
Order By: Relevance
“…It demonstrates the exact site of bile duct disruption and may allow stent placement in selected bile duct injuries. ERCP images show disruption of the bile duct wall and extravasation of contrast material [9].…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates the exact site of bile duct disruption and may allow stent placement in selected bile duct injuries. ERCP images show disruption of the bile duct wall and extravasation of contrast material [9].…”
Section: Discussionmentioning
confidence: 99%
“…The commonest complications were found infection and chest infection. 16 In present study, the complication rate was 32%. The commonest complication was Wound Infection followed by Respiratory complication and biliary fistula formation.…”
Section: Morbiditymentioning
confidence: 44%
“…It is suggested that the CT examination be performed with both intravenous and oral contrast. 17 This method was used for our patient, and even though the mesenteric infiltration and fluid suggested visceral trauma, the CT scan was inconclusive for pancreatic injury. Although CT scan may potentially identify a pancreatic laceration, it does not give information about the pancreatic duct.…”
Section: Discussionmentioning
confidence: 98%